ENTREVISTA COM PROFESSORAS(ES) DE FILOSOFIA DO ENSINO FUNDAMENTAL DO CEARÁ - Vale, Jocilaine Moreira Batista do; Cunha, Mario Jonny de Castro; Monteiro, Syssa Adley Rodrigues; Tôrres, Fabiana Martins; Sousa, Antônio Alex Pereira de; Lima, Paulo Willame Araújo de (Revista Dialectus - Revista de Filosofia, 2023)
ENTREVISTA COM PROFESSORAS(ES) DE FILOSOFIA DO ENSINO FUNDAMENTAL DO CEARÁ Com: Jocilaine Moreira Batista do Vale, Mario Jonny de Castro Cunha, Syssa Adley Rodrigues Monteiro, Fabiana Martins Tôrres Por: Antônio Alex Pereira de Sousa, Paulo Willame Araújo de Lim